Radiometric and geometric information content of TiungSAT-1 MSEIS Data - Hashim, Mazlan; Wan Kadir, Wan Hazli (Astronautic Technology (M) Sdn. Bhd., 2001)
In the last two decades, satellite remote sensed data have been widely used for assisting natural resources management and environmental protection works. in both application areas, there are various level of utilisation of remote sensing techniques. In most developed nations such techniques have been in place as an operational tool white in most developing countries effort are still underway to establish operational applications. This include Malaysia, where remote sensing application at user agencies are still at the semi-operational level due to various reasons. In the context of Malaysia, (in the late 70's to early 90's) the hindering factors can be categorised into: (1)lack of infrastructure and facilities to enable such applications of the technology to be optimised, and (2)lack of expertise within relevant organisations that enables them to undertake such applications. the former factor is now completely addressed with the government's emphasis on provide computing facilities within all user agencies, and in fact most of the relevant agencies already have minimum capacity to process satellite remote sensing data for specific applications. The latter is an on-going process satellite all relevant agencies where programmes to train personnel to the expert level are carried out as a long term commitment.